Health Care Services at Time of Natural Disasters: A Qualitative Study - HR. Khankeh; R. Mohammadi; F. Ahmadi (Iran University of Medical Sciences, 2007)
Background & Aim: The health care services have an essential role in saving human life at the time of disaster impact. Disasters always have prominent effects on health, public health and welfare of affected people. The way throu which health care services are delivered at the time of disaster impact is one of the most important challenges in crisis management. Although he Islamic Republic of Iran is the sixth-most disaster-prone country in the world and average of 4,000 people have killed and 55,000 affected annually by natural disasters over the last decade, a few studies about health care services at disasters have been done. Therefore, in this paper that is a part of a greater study, we have tried to explore how well the health care services at the time of disasters have been delivered.   Material & Method: This study is developed on the basis of grounded theory. Seventeen participants consisted of 5 nurses, 1 social worker, 1 psychologist, 2 psychiatrists, 1 general physician, 1 health professional, 1 epidemiologist, 1 master in health, 1 nurse aid and 3 Bam residents. All of them have at least one experience at disasters. Of those, 15 were male and 2 were female and their average age was 37. Semi-structured interviews and observational field note were used for data gathering. All of interviews were transcribed verbatim (word by word) and simultaneously constant comparative analysis was used according to Strauss and Corbin's method.   Result: The way of delivering health care services is one of the important concepts that implied from collected data of the study. This concept comprises four aspects: quality and quantity of health care services, equipment supplies, personnel situation and management. This concept represents the way of delivering health care services at the time of disasters. Unpleasant personnel situations, insufficient quality and quantity of health care services at the time of disaster, deficiencies of equipment and instrument, poor management and lack of coordination are the most important factors that hindered delivering comprehensive, continuous, accessible and qualified health care services at the time of disaster. Providing enough well educated and experienced personnel, enough and qualified health care services, enough instrument and equipments, and appropriate and coordinated management can facilitate on time, comprehensive, continuous and accessible health care services at the time of disasters.   Conclusion: Health sector mission of prevention, investigation and treatment of injured and sick people is more prominent in parallel with greater expectation of community at the time of disaster.,Health care services as the most significant foundation of crisis management should be delivered in a suitable and efficient way. Finally, the way of delivering health care services at the time of disaster was emphasized by participants in this study.